Making the Indian budget: how open and participatory? - Bhanu, Vinod (2007)
Open and participatory budget making is imperative for good governance; yet by international standards India fares badly on this count. This article analyses the process of budget preparation and suggests how it can be made more transparent and participatory. - Reproduced.
Keywords: Budget - India; Budget